2012
DOI: 10.1038/bjc.2012.456
|View full text |Cite
|
Sign up to set email alerts
|

Stage-dependent alterations of the serum cytokine pattern in colorectal carcinoma

Abstract: Background:Inflammation contributes to the pathogenesis of colorectal cancer (CRC), and cytokine levels are altered during colorectal carcinogenesis.Methods:The serum levels of 13 cytokines and their relation to clinical and pathological parameters, and systemic inflammatory response (mGPS, CRP and neutrophil–lymphocyte ratio), were analysed from a prospective series of 148 CRC patients and 86 healthy age- and sex-matched controls.Results:CRC patients had higher serum platelet-derived growth factor, interleuki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
243
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(257 citation statements)
references
References 49 publications
12
243
1
1
Order By: Relevance
“…These inflammatory cytokines may establish and keep a tumor microenvironment favoring aggressive tumor behavior. An elevated NLR is considered to be associated with elevated circulating concentrations of these cytokines, which offers an insight into mechanisms underlying an elevated NLR (30,31). Nevertheless, the cutoff points of NLR proposed in previous studies differ, including NLR thresholds of 2.3, 4.02 or 5 in gastric cancer (14,32,33), 0.38, 2.4 or 3 in colorectal cancer (15,34,35), 2.3 or 2.5 in NSCLC (10,36), and consensus has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory cytokines may establish and keep a tumor microenvironment favoring aggressive tumor behavior. An elevated NLR is considered to be associated with elevated circulating concentrations of these cytokines, which offers an insight into mechanisms underlying an elevated NLR (30,31). Nevertheless, the cutoff points of NLR proposed in previous studies differ, including NLR thresholds of 2.3, 4.02 or 5 in gastric cancer (14,32,33), 0.38, 2.4 or 3 in colorectal cancer (15,34,35), 2.3 or 2.5 in NSCLC (10,36), and consensus has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating IL-6 is commonly elevated in a number of cancers, including colorectal cancer (11)(12)(13), and is the predominant stimulus for the hepatic synthesis of acute phase proteins, including CRP (6). Cancer-associated fibroblasts and inflammatory cells contribute to high levels of IL-6 within the tumour microenvironment (14,15), with subsequent tumour cell activation of the soluble IL-6 receptor/ glycoprotein 130 complex (16).…”
Section: Introductionmentioning
confidence: 99%
“…The underlying molecular basis of NLR has found that there is an elevation in the levels of pro-inflammatory cytokines (e.g., IL-1ra, IL-6, IL-7, IL-8, IL-12) in the plasma of these patients. [11][12][13] Moreover, high peritumoral infiltration of macrophages was observed in cancer patients with elevated NLR. 12 Therefore, elevated NLR appears to be a good indicator of up-regulation of the innate immune response.…”
Section: Discussionmentioning
confidence: 99%